2018
DOI: 10.3892/mmr.2018.9594
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of klotho in adipose-derived stem cells protects against UVB-induced photoaging in co-cultured human fibroblasts

Abstract: Co-culture methods are widely used in tissue engineering to drive tissue formation with the direct or indirect interaction of multiple cell types. Klotho is a novel biomarker involved in aging. In this study, we evaluated the protective effects of klotho overexpressed adipose-derived stem cells (ADSCs) against ultraviolet radiation B (UVB)-induced photoaging in co-cultured human skin fibroblasts (HSF2 cell line). Furthermore, the involvement of P38 mitogen-activated protein kinase (MAPK) signaling was investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
0
7
0
3
Order By: Relevance
“…The molecular interaction between fibroblasts and the ECM is obstructed due to the decrease of collagen, which eventually results in the damage of fibroblast function and further collagen decrease [ 94 ]. It is reported that ADSC-Exo can promote the migration ability of HDFs irradiated by UVB [ 95 ], suppress the overexpression of MMP-1 [ 95 , 96 ], MMP-2 [ 95 , 97 ], MMP-3 [ 95 , 96 ], MMP-9 [ 92 , 95 ] and MMP-13 [ 97 ] caused by UVB. Moreover, it can increase collagen I, II, III, and V and elastin expression [ 92 , 95 ].…”
Section: Adscs Mechanisms In Photoagingmentioning
confidence: 99%
“…The molecular interaction between fibroblasts and the ECM is obstructed due to the decrease of collagen, which eventually results in the damage of fibroblast function and further collagen decrease [ 94 ]. It is reported that ADSC-Exo can promote the migration ability of HDFs irradiated by UVB [ 95 ], suppress the overexpression of MMP-1 [ 95 , 96 ], MMP-2 [ 95 , 97 ], MMP-3 [ 95 , 96 ], MMP-9 [ 92 , 95 ] and MMP-13 [ 97 ] caused by UVB. Moreover, it can increase collagen I, II, III, and V and elastin expression [ 92 , 95 ].…”
Section: Adscs Mechanisms In Photoagingmentioning
confidence: 99%
“…Kemungkinan tanah-tanah yang pori-porinya besar, permeabilitasnya mendekati nol (hampir tidak ada aliran), yaitu jika pori-pori tersebut terisolasi (tidak ada hubungan) sesamanya. Permeabilitas juga mungkin mendekati nol apabila (28,(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90) pori-pori tanah sangat kecil, seperti pada tanah liat. Sifat dari cairan yang secara langsung berpengaruh terhadap permeabilitas tanah adalah viskositas (viscosity) dan berat jenis (density).…”
Section: Persen Massaunclassified
“…Metode ini tergolong sederhana dan mudah diaplikasikan. Prinsip yang digunakan identik dengan cara yang dikemukakan De Boodtdan didasarkan pada hukum Darcy (39)(40)(41)(42)(43) .Secara kuantitatif permeabilitas tanah diartikan sebagai kecepatan bergeraknya suatu cairan pada suatu media berpori (28,(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90) dalam keadaan jenuh. Dalam hal ini sebagai cairan adalah air, dan sebagai media berpori adalah tanah .…”
Section: Konduktivitas Hidrolikunclassified
“…Kemungkinan tanah-tanah yang poriporinya besar, permeabilitasnya mendekati nol (hampir tidak ada aliran), yaitu jika pori-pori tersebut terisolasi (tidak ada hubungan) sesamanya. Permeabilitas juga mungkin mendekati nol apabila (28,(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90) pori-pori tanah sangat kecil, seperti pada tanah liat. Sifat dari cairan yang secara langsung berpengaruh terhadap permeabilitas tanah adalah viskositas (viscosity) dan berat jenis (density).…”
Section: Konduktivitas Hidrolikunclassified